Explaining U-shape of the Referral Hiring Pattern in a Search Model with Heterogeneous Workers - Anna Zaharieva; Yuliia Stupnytska (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper presents a search model with heterogeneous workers, social networks and endogenous search intensity. There are three job search channels available to the unemployed: costly formal applications and two costless informal channels - through family and professional networks. The gain from being employed is increasing in the productivity, so the lowest motivation for preparing formal applications is proved to be among the least productive worker types. We assume that professional contacts exhibit a strong degree of homophily, thus it is profitable for firms to direct their network search towards more productive incumbent employees. So the probability of a professional referral is increasing in the productivity of the worker, which mitigates the incentives to use the formal channel of search. Therefore, the model predicts that workers in the right (left) tail of the productivity distribution have the highest propensity of finding a job with a help of professional (family) contacts, whereas the formal channel of search is mostly utilized by workers in the middle range of the distribution. This explains the U-shaped referral hiring pattern in the model. Endogenous sorting of workers across channels also implies that professional (family) referrals are associated with wage premiums (penalties) compared to the formal channel of search.
Keywords: J23; J31; J64; 330